Hand Hygiene Self-Efficacy Scale for Preschool Children in Gamified Digital Intervention Project : Development and Preliminary Testing - Dangis, Glenda (My University, 2022)
To create a foundation for the success of hand hygiene interventions, determinants of hand hygiene behaviour should be examined. Self-efficacy is an important determinant that can influence the adoption and maintenance of hand hygiene behaviour. However, there is no validated instrument available to measure preschool children’s self-efficacy in hand hygiene. The aim of this study was to develop a scale that measures hand hygiene self-efficacy of preschool children (3 to 6 years old) in relation to hand hygiene behaviour in early childhood education and care settings. This study involved three parts. DeVellis’ Scale Development was used as the methodological framework to develop the scale. Part one was the generation of the item pool. Domain was identified by inductive and deductive methods. Literature reviews and a collection of previous study feedback were performed. Part two was the development of the Hand Hygiene Self-Efficacy Scale (HHSS). This part involved the two rounds of expert reviews and pre-test conduction using a cognitive interview. A qualitative descriptive method was performed to analyse the interview. Part three was the pilot test; the scale was administered for preliminary statistics. Descriptive statistics using t-test and ANOVA, reliability analysis using Cronbach’s alpha, and item analysis using item-total and inter-item statistics were performed using SPSS version 26. In part one, four indicators of self-efficacy were identified. Smiley faces and a three-point Likert type were created. Eleven items of interview type were generated. In part two, experts reviewed the item pool for content and construction. A cognitive interview was conducted with five children. Face validity and content validity were established. In part three, the scale was administered to 20 children. There was a significant difference in gender and language, but no significant difference in age. The scale has a good internal consistency with an alpha value of 0.77. Item discriminations were good with all the items’ value of more than 0.20. However, item correlations resulted in values of two negative -0.02 and -0.11, two weak 0.10 and 0.15, and four good items ranging from 0.20-0.62. To our knowledge, this will be the first Hand Hygiene Self-Efficacy Scale (HHSS) to be developed with a theoretical basis. This study established an initial step toward measuring the self-efficacy in hand hygiene of preschool children in early education and care settings. Further statistical testing of a bigger sample is needed for psychometric evaluation.

Jotta käsihygieniaan liittyvät interventiot voivat onnistua, on tarkasteltava käsihygieniakäyttäytymiseen liittyviä tekijöitä. Minäpystyvyys (self-efficacy) on tärkeä tekijä, käsihygieniakäyttäytymisen omaksumisessa ja ylläpidossa. Esikoululaisten käsihygieniaan liittyvän minäpystyvyyden mittaamiseen ei kuitenkaan ole vielä käytettävissä validoitua mittaria. Tutkimuksen tavoitteena oli kehittää mittari, joka mittaa esikoululaisten (3—6-vuotiaiden) käsihygieniaan liittyvää minäpystyvyyttä suhteessa käsihygieniakäyttäytymiseen varhaiskasvatuksessa ja hoitoympäristössä. Tämä tutkimus koostui kolmesta osasta. DeVellin Scale Development -teosta käytettiin metodologisena viitekehyksenä mittarin kehittämisessä. Tutkimuksen ensimmäisessä osassa luotiin kysymyspatteristo (item pool). Aihealueettunnistettiin induktiivisten ja deduktiivisten menetelmien avulla suorittamalla kirjallisuuskatsaus ja kokoamalla aiempia tutkimuspalautteita. Tutkimuksen toisessa osassa kehitettiin Hand Hygiene Self-Efficacy Scale (HHSS) -mittari. Toinen osa sisälsi kaksi asiantuntija-arviointia ja mittarin esitestaamisen kognitiivisten haastattelujen avulla. Haastattelut analysoitiin kuvailevan laadullisen menetelmän mukaan. Tutkimuksen kolmas osa oli mittarin pilotointi. Tutkimuksen ensimmäisessä osassa tunnistettiin neljä minäpystyvyyden indikaattoria. Toisessa osassa, asiantuntijat arvioivat kysymyspatteriston sisällön ja rakenteen. Viisi lasta osallistui haastatteluihin. Sisällönvaliditeetti todettiin päteväksi ja hyväksyttäväksi. Kolmannessa osiossa mittari pilotoitiin (n=20). Pilotin tulosten mukaan, mittarin sisäinen johdonmukaisuus on hyvällä tasolla (Cronbachin Alfa 0.77). Kysymysten erotteluvaliditeetti olivat hyvällä tasolla, kaikkien kysymysten ylittäessä arvon 0.20. Korrelaatiot vaihtelivat arvojen -0.02–0.62. välillä. Tietämyksemme mukaan tämä on ensimmäinen teoreettiseen viitekehykseen pohjautuen kehitetty mittari, joka mittaa käsihygieniaan liittyvää minäpystyvyyttä. Tämä tutkimus otti ensimmäiset askeleet kohti esikoululaisten käsihygieniaan liittyvän minäpystyvyyden mittaamista kohden. Mittarin psykometristä arviointia varten, mittaria tulee tulevaisuudessa testata suuremmalla osallistujamäärällä.
Keywords: self-efficacy, young children, hand hygiene, scale development, cognitive interview, reliability